SCHOOL MANAGEMENT STRATEGIES FOR IMPROVING THE QUALITY OF LEARNING IN THE DIGITAL ERA - Aditya, Dedy Yusuf; Ai Solihah; Gita Kencanawaty (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
School management plays a crucial role in improving the quality of learning in the digital era. The use of digital technology enables schools to enhance operational efficiency and improve the quality of the learning process. In this context, the implementation of information technology in academic management, digital-based curriculum management, and strengthening transformational leadership are key elements to support this transformation. Additionally, continuous training and technology-based supervision for teachers are essential to enhance teaching competencies and quality. Therefore, schools need to adopt innovative management strategies based on technology to meet the demands of education that continue to evolve in the digital era.